Assessing Genetic Overlap Between Platelet Parameters and Neurodegenerative Disorders - Tirozzi, Alfonsina; Izzi, Benedetta; Noro, Fabrizia; Marotta, Annalisa; Gianfagna, Francesco; Hoylaerts, Marc F.; Cerletti, Chiara; Donati, Maria Benedetta; de Gaetano, Giovanni; Iacoviello, Licia; Gialluisi, Alessandro (Frontiers in Immunology, 2020)
Neurodegenerative disorders like Parkinson (PD) and Alzheimer disease (AD) suffer from the lack of risk-predictive circulating biomarkers, and clinical diagnosis occurs only when symptoms are evident. Among potential biomarkers, platelet parameters have been associated with both disorders. However, these associations have been scarcely investigated at the genetic level. Here, we tested genome-wide coheritability based on common genetic variants between platelet parameters and PD/AD risk, through Linkage Disequilibrium Score Regression. This revealed a significant genetic correlation between platelet distribution width (PDW), an index of platelet size variability, and PD risk (rg (SE) = 0.080 (0.034); p = 0.019), which was confirmed by a summary-summary polygenic score analysis, where PDW explained a small but significant proportion PD risk (<1%). AD risk showed no significant correlations, although a negative trend was observed with PDW (rg (SE) =-0.088 (0.053); p=0.096), in line with previous epidemiological reports. These findings suggest the existence of limited shared genetic bases between PDW and PD, and warrant further investigations to clarify the genes involved in this relation. On the other side, they suggest that the association between platelet parameters and AD risk is more environmental in nature, prompting to investigate which factors may influence these traits.